2019
DOI: 10.3390/f10050369
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Nitrogen Addition Affects Soil Respiration and Belowground Organic Carbon Fraction for a Pinus tabuliformis Forest

Abstract: The capability of forest ecosystems to sequester carbon from the atmosphere largely depends on the interaction of soil organic matter and nitrogen, and thus, this process will be greatly influenced by nitrogen deposition under the future scenario of global change. To clarify this interaction, the current study explored the variations in soil carbon fraction and soil respiration with different levels of nitrogen deposition. NH4NO3 was added at concentrations of 0, 50, 100, 200, and 400 kg N ha−1 year−1 separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 75 publications
(132 reference statements)
0
17
1
Order By: Relevance
“…At present, a global meta-analysis showed that atmospheric N deposition negatively affects soil microbial growth, composition, function, and respiration across all terrestrial ecosystems; these negative effects increased with the N application rate and experimental duration [32]. However, the responses of soil respiration and microbial activities to N addition were inconsistent in previous studies [26], showing promotion [13,33,34], inhibition [16,35], and no effects [5,36]. The response of major microbial groups to N in terrestrial ecosystems was found to be mainly influenced by the duration and content of N inputs [17,37].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…At present, a global meta-analysis showed that atmospheric N deposition negatively affects soil microbial growth, composition, function, and respiration across all terrestrial ecosystems; these negative effects increased with the N application rate and experimental duration [32]. However, the responses of soil respiration and microbial activities to N addition were inconsistent in previous studies [26], showing promotion [13,33,34], inhibition [16,35], and no effects [5,36]. The response of major microbial groups to N in terrestrial ecosystems was found to be mainly influenced by the duration and content of N inputs [17,37].…”
Section: Introductionmentioning
confidence: 93%
“…N addition effects on microbial biomass (G + , B, MBC and MBN) were likely the most potent drivers of soil respiration, according to the RDA and SEM results. Third, increasing N availability benefited plant growth by enhancing new soil organic matter input, thus leading to an increase in soil respiration [16,43,44].…”
Section: Response Of Soil Respiration To N Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical N load is estimated to be between 8 and 10 g N m −2 year −1 [16]. Conversely, the SOC content was reduced following N addition in a Pinus tabuliformis forest [17] and Tibetan alpine meadow [18], especially in the 10-20 cm soil layer [19]. Research has found that N addition tends to enhance SOC mineralization [20].…”
Section: Introductionmentioning
confidence: 99%
“…3), which was much higher than that of 1.05 μmol CO 2 m -2 s -1 in spruce forest, 0.96μmol CO 2 m -2 s -1 in Abies forest (Wang et al 2019a), and the mean value of Chinese coniferous forest (2.32 μmol CO 2 m -2 s -1 ) (Dai et al 2015). In all treatments, the Rs of Larix gmelinii forest showed positive responses to low N treatment, which was different from other results (Wang et al 2019b;Zhang et al 2019b;Yan et al 2020). Zhong et al (2016) considered that forest was less affected by human activities, and had a balanced soil N cycle.…”
Section: Effects Of N Addition On Rsmentioning
confidence: 59%